Kidney and Urinary Tract Involvement in Epidermolysis Bullosa: Is Routine Follow-Up Necessary? - YÜCELTEN, AYŞE DENİZ; ALPAY, HARİKA; YILDIZ, NURDAN (MATTIOLI 1885, 2021)
Background: Several renal and urinary tract complications have been reported in patients with epidermolysis bullosa. Objective: This study investigated kidney and urinary tract involvement in patients with epidermolysis bullosa. Patients and Methods: Patients with epidermolysis bullosa in treatment at the Dermatology Unit were included in the study. Glomerular and tubular functions were investigated. Results: The study included 16 patients (4 females, 12 males) of mean 11.1 years (SD = 8.1 years). Estimated GFR was normal in all patients except one with end-stage renal disease. Excluding this patient, the urinary albumin/creatinine ratio and the fractional excretion of sodium were normal. The mean beta-2 microglobulin/creatinine ratio was 278.8 Rig, and it was abnormally high in 2 patients. The mean tubular phosphorus reabsorption was 92.6%; it was abnormally low in 1 patient. Severe kidney or urinary tract involvement was present in 2 patients with recessive dystrophic EB-generalized severe (RDEB-GS): one patient had obstructive bullous lesions in the urethra; the other had end-stage renal disease secondary to focal segmental glomeruloscierosis and was on peritoneal dialysis for 3 years. Conclusions: Assessment for renal and urinary tract involvement should become a routine part of the evaluation of patients with any type of ER, but especially of patients with RDEB-GS. Patients with mild tubular dysfunction need long-term follow-up to detect early deterioration of renal function.
Keywords: end stage renal disease; epidermolysis bullosa; peritoneal dialysis; urinary tract involvement; NEPHROTIC SYNDROME; RENAL AMYLOIDOSIS; IGA NEPHROPATHY; PATIENT; COMPLICATIONS; DISEASE; EXPERIENCE; SECONDARY